ROLE OF KETAMINE IN SUBANESTHETIC DOSE TO ALLEVIATE PROPOFOL INJECTION PAIN IN PATIENTS UNDERGOING CESAREAN SECTION SURGERY - Mohsin, Muhammad Usman; Ahmad, Mirza Shakeel; Israr, Humayun; Furqan, Aamir (Pakistan Armed Forces Medical Journal, 2018)
Objective: To evaluate the role of sub anesthetic dose of ketamine when given 5 minutes prior to Propofol injection in alleviating pain of injection during cesarean section surgery. Study Design: Randomized controlled trial. Place and Duration of Study: Department of anesthesia and critical care, Nishtar Hospital Multan, from Aug 2016 to Feb 2017. Material and Methods: A total number of 130 (100%) patients were included in the study. Data was analyzed using SPSS (v 23.2), mean and SD calculated for continuous data (age, BMI) and in continuous data was presented as frequency and percentages (ASA status, pain of propofol injection). Effect modification seen by applying chi square test and p-value ≤0.05 considered as significant. Results: A total number of 100% (n=130) patients were included in this study, all were females. The main outcome variable of this study was pain of propofol injection. It was observed that, in control group, 87.7% (n=57) patients complaints about pain after propofol injection and 12.13% (n=8) remain normal. But, in ketamine group only 16.9% (n=11) patients complaint about pain of propofol injection and 83.1% (n=54) were remained pain free. Conclusion: Administration of ketamine 0.25μg/kg five minutes before propofol injection is a safe and effective method in preventing propofol injection pain.